2015
DOI: 10.1614/wt-d-15-00061.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Cotton by Combinations of Microencapsulated Acetochlor and Various Residual Herbicides Applied Preemergence

Abstract: Residual herbicides are routinely recommended to aid in control of glyphosate-resistant (GR) Palmer amaranth in cotton. Acetochlor, a chloroacetamide herbicide, applied PRE, controls Palmer amaranth. A microencapsulated (ME) formulation of acetochlor is now registered for PRE application in cotton. Field research was conducted in North Carolina to evaluate cotton tolerance and Palmer amaranth control by acetochlor ME alone and in various combinations. Treatments, applied PRE, consisted of acetochlor ME, pendim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 51 publications
8
35
0
1
Order By: Relevance
“…], and soybean [Glycine max (L.) Merr.] to control annual grasses and small-seeded broadleaf weeds (Anonymous, 2017b;Cahoon et al 2015;Geier et al, 2009;Steckel et al, 2002). Acetochlor inhibits geranylgeranyl pyrophosphate cyclization enzymes, which are part of the gibberellin biosynthetic pathway and controls weeds by inhibiting growth of seedling shoots (Shaner, 2014).…”
Section: Peanut Is a Valuable Commodity In The Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…], and soybean [Glycine max (L.) Merr.] to control annual grasses and small-seeded broadleaf weeds (Anonymous, 2017b;Cahoon et al 2015;Geier et al, 2009;Steckel et al, 2002). Acetochlor inhibits geranylgeranyl pyrophosphate cyclization enzymes, which are part of the gibberellin biosynthetic pathway and controls weeds by inhibiting growth of seedling shoots (Shaner, 2014).…”
Section: Peanut Is a Valuable Commodity In The Unitedmentioning
confidence: 99%
“…Grichar et al (2015) reported no negative effect of acetochlor ME application timing and rate on peanut grade and yield in runner and Spanish market type cultivars. Cahoon et al (2015) documented that acetochlor ME applied PRE caused less than 8% early season injury to cotton and at least 90% control of Palmer amaranth. Early season injury caused by acetochlor was transient and did not negatively impact cotton yield.…”
Section: Peanut Is a Valuable Commodity In The Unitedmentioning
confidence: 99%
“…Several soil-residual PRE herbicides have been registered for Palmer amaranth control in maize. For instance, acetochlor, dimethenamid-P, pendimethalin, pyroxasulfone, saflufenacil, or S -metolachlor applied PRE provided >80% Palmer amaranth control up to 50 days after application (Johnson et al, 2012 ; Cahoon et al, 2015 ; Janak and Grichar, 2016 ; Meyer et al, 2016 ). In addition, some soil residual herbicides such as acetochlor, pyroxasulfone, or dimethenamid-P can be applied POST in maize up to certain growth stages (Anonymous, 2017e , f , g ).…”
Section: Introductionmentioning
confidence: 99%
“…In Georgia, 18 573 kg of fomesafen was applied on 66 636 ha in 2007 and this increased to 85 164 kg on 304 330 ha by 2015 . However, cotton growers in the southern USA have frequently observed seedling injury, stunting and stand reduction caused by fomesafen application and little analytical data are available to address this issue . Fomesafen has recently received a 24C special local need label for Palmer amaranth control in several vegetables in Georgia, such as watermelon, tomatoes, squash and pepper.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, cotton growers in the southern USA have frequently observed seedling injury, stunting and stand reduction caused by fomesafen application and little analytical data are available to address this issue. [20][21][22] Fomesafen has recently received a 24C special local need label for Palmer amaranth control in several vegetables in Georgia, such as watermelon, tomatoes, squash and pepper. However, because of its relatively long soil persistence, fomesafen carryover injury on the subsequent sensitive crop planted in the same bed has also been reported by Georgia vegetable growers who utilize plasticulture in their production.…”
Section: Introductionmentioning
confidence: 99%